MANAGEMENT OF PORTAL VEIN THROMBOSIS IN CIRRHOTIC PATIENTS - Maria Anna Guardascione; Lucio Amitrano (Mediterranean Journal of Hematology and Infectious Diseases)
Portal vein thrombosis (PVT) not associated with hepatocellular carcinoma is considered a frequent complication of liver cirrhosis but, unlike PVT occurring in non-cirrhotic patients, very few data are available on its natural history and management. The reduced portal blood flow velocity is the main determinant of PVT but, as in other venous thromboses, multiple factors local and systemic, inherited or acquired often can concur with. PVT has a variety of clinical presentations ranging from asymptomatic to life-threatening diseases like gastroesophageal bleeding or acute intestinal ischemia. It is usually diagnosed by Doppler ultrasound but computed tomography and magnetic resonance imaging are useful to study the extent of thrombosis and the involvement of the abdominal organs. The risk of bleeding mainly determined by the presence of gastroesophageal varices and clotting alterations causes concern for the treatment of PVT in cirrhotic patients. To date, anticoagulant therapy seems to be indicated only in patients awaiting liver transplantation. This review focuses on the definition of the subgroups of patients with cirrhosis that might benefit from treatment of PVT and examines the pros and cons of the available treatments in terms of efficacy, monitoring and safety, providing also perspectives for future studies.